Liquid Metals - Jerold Samuel Chelladurai, Samson; Gnanasekaran, S.; Mayilswamy, Suresh (IntechOpen, 2021)
This book discusses liquid metals used in various manufacturing processes in the aerospace and automobile industries. It provides important original and theoretical experimental results on the use of non-routine technologies. It also presents novel applications of more familiar experimental techniques and analyses of composites. Topics covered include the importance of liquid metals, friction stir welding to improve aluminium alloys, adhesion phenomenon of liquid metals, secondary aluminium used for producing products, and more.